Back-projecting secondary craters using a cone of uncertainty. (February 2019) - Naegeli, Timothy J.; Laura, Jason
Abstract: In this paper we present an extension to the Large Crater Clustering (LCC) tool set which places a cone of uncertainty around the trajectories of secondary impact craters to determine potential locations of source craters. The LCC tool set was a first step in the spatial quantification of primary and secondary cratering processes, which allows planetary geologists to accurately estimate the geologic age of a celestial surface. This work builds on the LCC tool set by accounting for the ambiguity of flight path trajectories through a Python script that leverages ArcGIS's ArcPy library. We chronicle the mechanics of the script, which creates geodetically correct cones then counts them within equally sized cells of a vector grid. We describe the process that was used to derive the shape of the cone and provide parameters for the sizes of the cones and the grid. We demonstrate that the cone of uncertainty has the ability to compensate for error in secondary crater trajectories by introducing deviation in the trajectory bearing and comparing the predicted primary crater location. We use two study areas on Mars as well as the entire lunar surface to illustrate the usefulness of the extension as an aid to human interpretation of back-projections. Highlights: The inclusion of spatial uncertainty into impact ejecta trajectories is proposed. A Python script is developed as an extension to the LCC tool set. The cone of certainty can be used to predict primary crater locations. Three cases studies are presented.